Cable it's not just for TV. - Dutta-Roy, A. (IEEE spectrum)
Hybrid fiber-coaxial-cable systems can download data from the Internet at up to 30 Mb/s while also carrying multiple telephone channels and broadcast radio and TV signals-both analog and digital. This paper concentrates on single-access technology-cable modems. The cable modem packs the Internet data in the form of 10BASE-T frames, which are fed over an Rj-45 connection to the Ethernet network interface card (NIC) in a computer. The phone connections at the cable modem are for Internet protocol (IP) telephony, which has yet to come to residences in a big way. The connection between a cable modem and the Internet is packet-switched and so the link is always active. The standards for cable modems are discussed as is the sending of digitised voice over a packetised system